The Influence of Real-time Marketing Campaigns of Retailers on Consumer Purchase Behavior - Kallier, Safura M. (International Review of Management and Marketing, 2017)
The rapid advancements in technology have provided retailers with various methods of communicating with the customer such as real-time marketing. Real-time marketing (RTM) allows retailers to interact with customers through various means in real time. Although many businesses are starting to adapt real-time marketing as a marketing tool in their businesses, the influence of real-time marketing on consumer purchase behaviour has not been investigated. The primary purpose of this study was therefore to determine the influence of real-time marketing campaigns of retailers on consumer purchase behaviour in South Africa. An empirical study was conducted, in which data was collected from consumers of retail stores in the Gauteng province of South Africa by means of a web-based (computer-assisted), self-administered questionnaire. A quantitative approach was followed in order to satisfy the research objectives of the study. The study found that RTM campaigns that were personalised and offered immediate discounts influenced consumers behaviours. Keywords: Real-time marketing; consumer behaviour; retailers; technology JEL Classifications: M30; M31